Influencia de las macrófitas sobre la estructura poblacional de rotíferos y microscrustáceos en un plano de inundación tropical - Lucía Villabona-González, Silvia (2011)
Most studies on zooplankton ecology have been conducted in open waters. However, it has been consid-ered of great importance to extend such studies to other habitats, such as those generated of macrophytes. We studied the spatial and temporal variation of the microcrustacean and rotifer assemblage structures associated with macrophytes, and compare them with the variation exhibited in open waters. Integrated samples were col-lected for zooplankton and phytoplankton biomass using a Schindler bottle, in four open water sites and four other sites covered by macrophytes in the floodplain complex of Ayapel (Córdoba, Colombia) during different limnimetric levels. The significant differences in the structure were evaluated using Kruskal & Wallis and discriminant analyses, and the similarity among sampling sites was evaluated using Bray & Curtis analysis. Zooplanktonic richness was favored by macrophytes. However, we did not find a constant spatial pattern for density, and only particular trends apparently conditionated by flood pulses. The presence of Eichhornia azurea(Pontederiaceae) contributed in a significant way with an increase in the diversity and density of benthic taxa. The density of some zooplanktonic groups was related with environmental conditions and phytoplanktonic biomass.